2022
DOI: 10.33545/26646021.2022.v4.i2b.181
|View full text |Cite
|
Sign up to set email alerts
|

The duke lacrosse scandal and ethics in prosecution

Abstract: Ethics is one of the most critical issues for those who hold public offices, whether elected, appointive, or in the civil service. The issue is fundamental in the criminal justice sector since people's lives, livelihoods, and liberty are at stake whenever individuals negatively interact with the criminal justice system. Wrong accusations, being followed by unfair convictions, can usually lead to a person losing decades of their life, for which there can never be compensation enough to cure the emotional pain a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…Insecure people tend Open Journal of Political Science to engage in battles both for psychological and political reasons. Nevertheless, human nature constitutes aggression, ego, and the need to acquire more, whereby competition inspires the ego (Tzenios, 2022); the ego gets a kick out of the perks. Wars are a transaction in which the costs of war must not considerably outweigh the benefits.…”
Section: The One Leading War Is Always Rightmentioning
confidence: 99%
“…Insecure people tend Open Journal of Political Science to engage in battles both for psychological and political reasons. Nevertheless, human nature constitutes aggression, ego, and the need to acquire more, whereby competition inspires the ego (Tzenios, 2022); the ego gets a kick out of the perks. Wars are a transaction in which the costs of war must not considerably outweigh the benefits.…”
Section: The One Leading War Is Always Rightmentioning
confidence: 99%
“…There is also evidence that infection in children and adults leads to different pathology. 28 This variation in outcome seems to be related to the severity and the anatomical distribution of the gastritis attributable to H pylori. 29 Patients who have duodenal ulcer with antrumdominant H pylori gastritis and only very lowgrade corpus H pylori gastritis retain normal (or even high) acid secretion, and they very rarely develop gastric carcinoma, 30,31 whereas individuals with extensive corpus gastritis develop hypochlorhydria and gastric atrophy.…”
Section: Role Of H Pylorimentioning
confidence: 99%
“…Initial analysis showed that 89% of histological sections of patients with stomach cancer of intestinal type contained H pylori in noncancerous tissue compared with 32% in diffuse type cancer; 25 however, results of serological analysis showed an association between H pylori and both types of gastric cancer.26,27 The association between cancer of the gastric cardia and H pylori infection is ambiguous.H pylori infection is associated with various clinical outcomes, including gastric cancer and duodenal ulcer disease. There is also evidence that infection in children and adults leads to different pathology 28. This variation in outcome seems to be related to the severity and the anatomical distribution of the gastritis attributable to H pylori 29.…”
mentioning
confidence: 99%
“…mercaptopurine) [13][14][15][16][17]. These two types of treatments are generally used in conjunction with each other depending on the treatment type, such as neoadjuvant therapy (pre-surgery), adjuvant therapy (following surgery) and concomitant therapy (radiotherapy and chemotherapy used together without surgical intervention) [18,19]. Pairing the chemotherapy and radiation therapy together allows for the cancer to be attacked by multiple approaches and can help prevent cancer cells from becoming resistant to either treatment.…”
Section: Traditional Cancer Therapiesmentioning
confidence: 99%